Pumps & pump systems II - Pienta, Gretchen; Elmaddah, Sherif (American Society of Plumbing Engineers, 2015)
"Designed to provide accurate and authoritative information for the design and specification of plumbing systems"--Page i.
Includes index.
Keywords: Pumping machinery.; elektronické knihy; electronic books